2023
DOI: 10.3390/molecules28124672
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Inhibitors as Therapeutic Agents Targeting Oncogenic Fusion Proteins: Current Status and Clinical

Abstract: Oncogenic fusion proteins, arising from chromosomal rearrangements, have emerged as prominent drivers of tumorigenesis and crucial therapeutic targets in cancer research. In recent years, the potential of small molecular inhibitors in selectively targeting fusion proteins has exhibited significant prospects, offering a novel approach to combat malignancies harboring these aberrant molecular entities. This review provides a comprehensive overview of the current state of small molecular inhibitors as therapeutic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 273 publications
0
3
0
Order By: Relevance
“…Advancing our understanding of the dynamic nature and constituent elements of the signal niche, as well as its communication with downstream targets, will provide valuable insights into the molecular mechanisms governing the aberrant Ras/MAPK signaling cascade driven by the CCDC6-RET fusion. Furthermore, we found that a significant proportion of RET fusion proteins, including KIF5B-RET and NCOA4-RET, possess the coiled-coil domain within their fusion partners ( 72 74 ). This observation raises the intriguing possibility that RET fusion proteins may recruit signaling proteins via LLPS, thereby contributing to the promotion of cancers.…”
Section: Discussionmentioning
confidence: 93%
“…Advancing our understanding of the dynamic nature and constituent elements of the signal niche, as well as its communication with downstream targets, will provide valuable insights into the molecular mechanisms governing the aberrant Ras/MAPK signaling cascade driven by the CCDC6-RET fusion. Furthermore, we found that a significant proportion of RET fusion proteins, including KIF5B-RET and NCOA4-RET, possess the coiled-coil domain within their fusion partners ( 72 74 ). This observation raises the intriguing possibility that RET fusion proteins may recruit signaling proteins via LLPS, thereby contributing to the promotion of cancers.…”
Section: Discussionmentioning
confidence: 93%
“…Evidence suggests that BCR-ABL proteins are present in granule-like structures in myeloid and lymphoid cells 53 , 54 . These BCR-ABL proteins are predicted to possess long IDRs, which endow weak multivalency and potentially facilitate phase separation and granule formation 55 , 56 . Kashiwagi et al revealed that BCR-ABL-positive granules were SGs 57 .…”
Section: Llps In Leukemia and Myelomamentioning
confidence: 99%
“…In recent years, oncogenic fusion genes have been identified in various cancer types because of the recent undertaking of extensive genomic analyses of clinical samples [ 1 , 2 , 3 ]. These oncogenic fusions may serve as potential therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…These oncogenic fusions may serve as potential therapeutic targets. In particular, fusion genes comprising the kinase domains of druggable receptor tyrosine kinases (RTKs), such as epidermal growth factor receptors or anaplastic lymphoma kinases, are used clinically as favorable therapeutic targets against malignancies [ 2 , 4 , 5 , 6 ]. Therefore, screening for oncogenic fusions is important for the diagnosis and treatment of cancers.…”
Section: Introductionmentioning
confidence: 99%